Phylogenomic Analysis of micro-RNA Involved in Juvenile to Flowering-Stage Transition in Photophilic Rice and Its Sister Species - Prasanta K. Dash; Payal Gupta; Rohini Sreevathsa; Sharat Kumar Pradhan; Tenkabailu Dharmanna Sanjay; Mihir Ranjan Mohanty; Pravat K. Roul; Nagendra K. Singh; Rhitu Rai (Cells, 2023)
Vegetative to reproductive phase transition in phototropic plants is an important developmental process and is sequentially mediated by the expression of micro-RNA MIR172. To obtain insight into the evolution, adaptation, and function of MIR172 in photophilic rice and its wild relatives, we analyzed the genescape of a 100 kb segment harboring MIR172 homologs from 11 genomes. The expression analysis of MIR172 revealed its incremental accumulation from the 2-leaf to 10-leaf stage, with maximum expression coinciding with the flag-leaf stage in rice. Nonetheless, the microsynteny analysis of MIR172s revealed collinearity within the genus Oryza, but a loss of synteny was observed in (i) MIR172A in O. barthii (AA) and O. glaberima (AA); (ii) MIR172B in O. brachyantha (FF); and (iii) MIR172C in O. punctata (BB). Phylogenetic analysis of precursor sequences/region of MIR172 revealed a distinct tri-modal clade of evolution. The genomic information generated in this investigation through comparative analysis of MIRNA, suggests mature MIR172s to have evolved in a disruptive and conservative mode amongst all Oryza species with a common origin of descent. Further, the phylogenomic delineation provided an insight into the adaptation and molecular evolution of MIR172 to changing environmental conditions (biotic and abiotic) of phototropic rice through natural selection and the opportunity to harness untapped genomic regions from rice wild relatives (RWR).